My Father's People : A Family of Southern Jews - Rubin, Louis D., Jr. (Louis Decimus), 1923-2013 (Book collections on Project MUSE., 2002)
Louis Rubin's people on his father's side were odd, inscrutable, and remarkable. In contrast to his mother's family, who were "normal, good people devoid of mystery," the ways of the Rubins both puzzled and attracted him. In My Father's People, Rubin tells "as best I can about them all - my father, his three brothers, and his three sisters." It is a searching, sensitive story of Americanization, assimilation, and the displacement - and survival - of a religious heritage. Born between 1888 and 1902 in Charleston, South Carolina, their father an immigrant Russian Jew, the Rubin children suffered